ISLAMIC RELIGIOUS EDUCATION FOR THE NEXT GENERATION: INSIGHTS FROM SURAH LUQMAN - Achmad Harristhana Mauldfi Sastraatmadja,; Khalid Ramdhani,; Siti Khulasoh, (Journal of Innovation Research and Knowledge, 2025)
Abstract: This study investigates the integration of the moral, spiritual, and ethical teachings of Surah Luqman (31:12-19) into contemporary Islamic education. The research aims to explore how these teachings can inform the development of moral and ethical frameworks within educational institutions, fostering well-rounded individuals. Employing a qualitative research design, the study analyzes the verses of Surah Luqman alongside relevant scholarly literature on Islamic education, character development, and the role of Tauhid, parental responsibility, and character education in shaping students’ moral outlook. The findings reveal that Surah Luqman offers a comprehensive guide for character formation, emphasizing values such as humility, respect for parents, patience, and gratitude. The study further highlights the successful integration of these teachings in pesantren and other Islamic educational settings, where character education is seen as equally important as academic achievement. Despite challenges in incorporating these teachings into secular education systems, the universal moral lessons from Surah Luqman remain applicable across diverse educational contexts. The study concludes by advocating for the integration of Surah Luqman into broader educational frameworks to foster moral, intellectual, and spiritual growth in students